THE GEOGRAPHY OF INTERNATIONAL STUDENTS IN LATVIA’S HIGHER EDUCATION: PREROGATIVE OR ‘SECOND CHANCE’ - Apsite-Berina, Elina; Robate, Liga Daniela; Krisjane, Zaiga; Burgmanis, Girts (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This paper links geographies of in-flow international students to the higher education system in Latvia and destination country choice rationales. Latvia welcomes international students from diverse geographies. Besides specific sourcing countries like Germany and India, there are also considerably constant and stable flows from former Soviet countries. International students are both an essential source of revenue for higher education institutions and to some extent, replacement of decrease of local students. This study adopts a mixed-method approach and based on the analysis of official statistical data and survey data. The survey reveals views on decision-making process and motives of current full-time international students in Latvia. The results indicate that to an extent, geography sets the main motives for study choice in Latvia. Seldom Latvia is set as the only priority destination country. On the one hand, among others balanced costs and accessibility of quality education in English attract foreign students, thus providing ‘second chance’ to be successful. On the other hand, Latvia gives the prerogative to have education in the European Union which for long-distance travelled students is a life-time opportunity.